2022
DOI: 10.3390/ijerph192114274
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Asthma, Atopic Dermatitis, and Allergic Rhinitis in Korean Adults before and during the COVID-19 Pandemic Using Data from the Korea National Health and Nutrition Examination Survey

Abstract: The prevalence of allergic diseases has been increasing globally prior to COVID-19. The pandemic resulted in changes in lifestyle and personal habits such as universal mask-wearing and social distancing. However, there is insufficient information on the impact of the COVID-19 pandemic on the prevalence of allergic conditions such as asthma, atopic dermatitis, and allergic rhinitis. We analyzed the incidence rate for self-reported and doctor-diagnosed cases of allergic diseases of asthma, atopic dermatitis, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 53 publications
1
5
0
Order By: Relevance
“…Notably, there was no difference between the two genders across different age groups and ethnicities before and after the COVID-19 pandemic. In congruence with a recent study done in Korea, there is no significant change in the AR prevalence between genders when comparing the number of cases among adults between 2019 and 2020 [ 30 ].…”
Section: Discussionsupporting
confidence: 83%
“…Notably, there was no difference between the two genders across different age groups and ethnicities before and after the COVID-19 pandemic. In congruence with a recent study done in Korea, there is no significant change in the AR prevalence between genders when comparing the number of cases among adults between 2019 and 2020 [ 30 ].…”
Section: Discussionsupporting
confidence: 83%
“…However, SARS-CoV-2 infection was not found to be causally associated with allergic diseases, and severe COVID-19 did not in turn lead to an increase or decrease in the risk of the allergic disease. The Korea National Health and Nutrition Examination Survey also did not show a significant reduction in the incidence of each allergic disease (asthma, AD, AR), whether self-reported or physician-diagnosed, in 2020 compared with 2019 27 . Although COVID-19 does not cause allergic diseases, viral infections (not just SARS-CoV-2) may exacerbate the symptoms of allergic diseases, so telemedicine is still advised during the COVID-19 pandemic 28 .…”
Section: Discussionmentioning
confidence: 87%
“…New diagnoses of atopic dermatitis also fell slightly 43 . As mentioned above, no significant decrease was shown in the incidence rates of allergic diseases (asthma, AD, AR) in Korea 27 . However, data from the nationally representative Korean Adolescent Risk Behavior Survey presented that the prevalence of allergy among Korean adolescents increased before 2019, but decreased significantly in 2020 44 .…”
Section: Discussionmentioning
confidence: 88%
“…Choi, H.G. et al [21] analyzed the frequency rate of self-reported and physician-diagnosed allergic diseases of asthma, atopic dermatitis, and allergic rhinitis in the Korean population. A total of 15,469 individuals were analyzed in the National Health and Nutrition Examination Survey dataset.…”
Section: Discussionmentioning
confidence: 99%